Effect of GSTA1 Variants on Busulfan-Based Conditioning Regimen Prior to Allogenic Hematopoietic Stem-Cell Transplantation in Pediatric Asians - Ai-Hoc Nguyen; Mohitosh Biswas; Apichaya Puangpetch; Santirhat Prommas; Samart Pakakasama; Usanarat Anurathapan; Jiratha Rachanakul; Rattanaporn Sukprasong; Nutthan Nuntharadtanaphong; Nutcha Jongjitsook; Suradej Hongeng; Chonlaphat Sukasem (Pharmaceutics, 2022)
Busulfan is widely used as a chemotherapy treatment before hematopoietic stem-cell transplantation (HSCT). However, the response of busulfan is highly variable and unpredictable, whereby the pharmacogenetic interference of glutathione S-transferase (GST) has strong evidence in Caucasians and some adult Asians but not in pediatric Asian patients. This study was aimed at investigating the associations of GST genetic polymorphisms with variations in the pharmacokinetic (PK) properties of busulfan in pediatric Asian patients. This retrospective cohort study recruited 92 pediatric patients. The polymorphism of GSTA1 was genotyped by Sanger sequencing, and GSTM1 and GSTP1 were genotyped by real-time PCR. Drug concentration and PK estimation were identified using an LC-MS/MS method and a noncompartmental model. Statistical analysis was performed by R software. Out of 92 patients, 48 (53%) were males, the mean age was 8.4 ± 5.12 years old, and the average weight was 26.52 ± 14.75 kg. The allele frequencies of GSTA1*B and of GSTM1 and GSTP1* deletions were 16.9%, 68.5%, and 21.2%, respectively. Patients with GSTA1*B had a statistically significant impact on the PK of busulfan, whereas those with GSTM1 and GSTP1 did not (p > 0.05). The carriers of GSTA1*B showed a significant difference compared to noncarriers in terms of t1/2 (for first dose: 161.9 vs. 134.3 min, p = 0.0016; for second dose: 156.1 vs. 129.8, p = 0.012), CL (88.74 vs. 124.23 mL/min, p = 0.0089), Cmax (4232.6 vs. 3675.5 ng/mL, p = 0.0021), and AUC (5310.6 vs. 4177.1 µM/min, p = 0.00033). The augmentation of AUC was around 27.1% in patients carrying the GSTA1*B variant. The GSTA1 polymorphism was significantly associated with variations of the pharmacokinetic properties of busulfan treatment in pediatric Asian patients.